THE BIOLOGY OF CANADIAN WEEDS.: 65. Salsola pestifer A. Nels. - CROMPTON, C. W.; BASSETT, I. J. (Canadian Journal of Plant Science, 1985)
In Canada, Russian thistle (Salsola pestifer A. Nels.) occurs in disturbed habitats in every province except Newfoundland. A key that separates three other closely elated species, Salsola kali L., S. collina Pall, and S. paulsenii Litv. is provided. Salsola kali occurs mainly on sandy beaches in the Maritime Provinces. S. collina is spreading in the province of Saskatchewan along railway tracks. It has recently been discovered in Ontario. Both S. collina and S. paulsenii are weedy in the adjacent western or in the southwestern United States, respectively. The biology of S. pestifer, the most common weedy species in the genus, is discussed.Key words: Weed biology, Salsola pestifer, Russian thistle